Predictive accuracy of perceived baby birth size for birth weight: a cross-sectional study from the 2016 Ethiopian Demographic and Health Survey - Dabere Nigatu; Demewoz Haile; Bereket Gebremichael; Yordanos M Tiruneh (BMJ Open)
Objectives The study was designed to evaluate the accuracy of maternally perceived baby birth size assessments as a measure of birth weight and examine factors influencing the accuracy of maternal size assessments.Study design Cross-sectional study.Setting The study is based on national data from the 2016 Ethiopian Demographic and Health Survey.Participants We included 1455 children who had both birth size and birth weight data.Main outcome measures Predictive accuracy of baby birth size for low birth weight. Level of discordance between maternally perceived birth size and birth weight including factors influencing discordance.Results Mother-reported baby birth size had low sensitivity (57%) and positive predictive value (41%) to indicate low birth weight but had high specificity (89%) and negative predictive values (94%). The per cent of agreement between birth weight (<2500 g vs ≥2500 g) and maternally perceived birth size (small size vs average or above) was 86% and kappa statistics indicated a moderate level of agreement (kappa=0.41, p<0.001). Maternal age, wealth index quintile, marital status and maternal education were significant predictors of the discordance between birth size and birth weight.Conclusions Maternal assessment of baby size at birth is an inaccurate proxy indicator of low birth weight in Ethiopia. Therefore, a mother’s recall of birth size should be used as a proxy indicator for low birth weight with caution and should take maternal characteristics into consideration.